2000
DOI: 10.1093/chromsci/38.8.345
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Sweeteners and Preservatives in Preserved Fruits by Micellar Electrokinetic Capillary Chromatography

Abstract: A micellar electrokinetic capillary method for the simultaneous determination of the sweeteners dulcin, aspartame, saccharin, and acesulfame-K and the preservatives sorbic acid; benzoic acid; sodium dehydroacetate; and methyl-, ethyl-, propyl-, isopropyl-, butyl-, and isobutyl-p-hydroxybenzoate in preserved fruits is developed. These additives are ion-paired and extracted using sonication followed by solid-phase extraction from the sample. Separation is achieved using a 57-cm fused-silica capillary with a buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Alkyl esters of p-hydroxybenzoic acid (parabens) are widely used as ingredients of pharmaceuticals, shampoos, liquid bath admixtures, skin care products, dental care products, soaps, sun screen agents, and hair styling products. Parabens can also be found in some drugs and foodstuffs, to preserve them from microbial attack (Lin and Choong 1999;Lin et al 2000;Soni et al 2005;Gryglik et al 2009;Błedzka et al 2012;Błędzka et al 2014). There is very little solid evidence regarding the extent parabens are absorbed and the resulting effects on male reproduction (endocrine disruptors).…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl esters of p-hydroxybenzoic acid (parabens) are widely used as ingredients of pharmaceuticals, shampoos, liquid bath admixtures, skin care products, dental care products, soaps, sun screen agents, and hair styling products. Parabens can also be found in some drugs and foodstuffs, to preserve them from microbial attack (Lin and Choong 1999;Lin et al 2000;Soni et al 2005;Gryglik et al 2009;Błedzka et al 2012;Błędzka et al 2014). There is very little solid evidence regarding the extent parabens are absorbed and the resulting effects on male reproduction (endocrine disruptors).…”
Section: Introductionmentioning
confidence: 99%
“…The calibration curves exhibited good linearity in the range of 90-1220 µg/mL with r of 0.9996 for C, 80-1120 µg/mL with r of 0.9998 (DMC), and 80-1200 µg/mL with r of 0.9998 (BDMC). [28] Analysis of curcuminoids in some Curcuma genus which are indigenous to Indonesia, namely, C. manga Val. and v. Zijp, C. heyneana Val.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Curcumin was also found to increase intestinal lipase, sucrose, and maltase activity. [61,62] Lin et al [28] have reported that curcumin suppresses intestinal fibrosis by inhibition of PPARΓ-mediated epithelial-mesenchymal transition. Zhang et al [63] have carried out experiment on the protective effect of curcumin on TNBS-induced intestinal inflammation which is mediated through the JAK/STAT pathway and reported excellent results.…”
Section: Action On Gastrointestinal Systemmentioning
confidence: 99%
“…Sodium *Corresponding author. E-mail: yyamini@modares.ac.ir benzoate (SB) and alkyl esters of p-hydroxybenzoic acid (parabens) including methylparaben (MP) and propylparaben (PP) are usually used as preservatives to prevent foods, cosmetics, and pharmaceuticals from microbial and fungal attacks [3][4][5][6][7]. Their toxicity is generally low owing to fast hydrolysis in vivo to parent acid, which is rapidly conjugated and excreted [8].…”
Section: Introductionmentioning
confidence: 99%